PENDAMPINGAN PEMBELAJARAN MATEMATIKA SMP MELALUI LESSON STUDY FOR LEARNING COMMUNITY (LSLC) DI SMPN 3 GRESIK - Irwani Zawawi; Churun Lu’lu’il Maknun (LPPM Universitas Bina Bangsa, 2023)
Collaboration and student-centred learning must be made into a culture in the learning process. Lesson study activities are movements that can facilitate this so that lesson study needs to be known in the school environment, especially teachers and students. Based on these problems, it is essential to carry out a model for developing the teaching profession by implementing lesson study. The method used in carrying out this activity is the method of discussion, mentoring and direct practice in class. The results of this activity are: 1) Improving the ability of teachers to develop learning tools that emphasize students' 4C (Critical Thinking, Creative, Communicative and Collaborative) abilities. 2) Improving teachers' abilities in developing IT-based learning media, 3) Improving the teacher's ability to manage learning in the classroom so that learning is no longer conventional, students actively discuss and work on assignments in collaboration. This activity was carried out at a junior high school in Gresik and was carried out according to the set targets. This activity impacts math teachers so that they can understand the concept of lesson study and practice the designs that have been designed in the Open Class activities. Activities are carried out to improve the quality of the learning process and the school. All teachers participating in the assistance can apply Lesson Study so that it is targeted to encourage increased learning and students' abilities in mathematics